Общие подходы к оценке и обеспечению защищенности бронекорпусов легких по массе машин - Бусяк, Юрий Митрофанович; Ткачук, Николай Николаевич; Васильев, Антон Юрьевич; Литвиненко, Александр Витальевич; Мазур, Игорь Витальевич; Даньшин, Ю. А.; Шаталов, Олег Евгеньевич (Национальный технический университет "Харьковский политехнический институт", 2014)
Стаття містить загальну постановку задачі забезпечення бронезахищеності корпусів легкоброньованих машин. Описані загальні підходи до її розв'язання. Крім того, сформульована задача проектно-технологічного забезпечення бронестійкості.

This paper contains a general statement of problem to ensure armoring protectability for lightly armored ve-hicles hulls. The general approaches are described to its solution. In addition, the problem of design and techno-logical support for armoring durability is formulated.
General approaches for estimating and ensuring the protectability of light-weight vehicles hulls
Keywords: легкобронированные машины; бронекорпус; бронезащищенность корпуса; кинетические боеприпасы; бронепробитие; военная техника